Recommendations of the AGG (Task Force for Obstetrics, Section Maternal Diseases) on the Management of Maternal Hepatitis B, C and D Infection in Pregnancy - Kühnert, Maritta; Kehl, Sven; Pecks, Ulrich; Schäfer-Graf, Ute Margaretha; Groten, Tanja; Schild, Ralf Lothar; Schlembach, Dietmar; Schmidt, Markus; Hamza, Amr (Geburtshilfe und Frauenheilkunde, 2021)
These statements and recommendations should provide appropriate information about maternal and fetal routes of infection, screening, detection of risk factors, diagnostic procedures, treatment, birth planning and peripartum and postpartum management of maternal hepatitis infection and offer pointers for prenatal counselling and routine clinical care on delivery wards.
CRIS-Team Scopus Importer:2021-05-21
Keywords: delivery; hepatitis; pregnancy; puerperium; viral infection